Photoluminescence and Structural Analysis of Er3+/Yb3+/Tm3+ Triply Doped Gd2O3 - Durante, Lorena P. B.; Rocha, Leonardo A.; Machado, Wagner S.; Martelli, Patricia B.; Schiavon, Marco A.; Manzani, Danilo; Pecoraro, Edison; Ribeiro, Sidney Jose L.; Ferrari, Jefferson L. (Brazilian Chemical Soc, 2017)
Spectroscopic and structural properties of Er3+:Yb3+:Tm3+ triply doped Gd2O3 nanocrystals were investigated. The effect of heat treatment at 800, 900, 1000 and 1100 degrees C for 4h, on the luminescence and the energy upconversion emissions (excited at 980nm) in the visible and near infrared spectral regions was discussed. The doping process with RE3+ was effective on Gd2O3 cubic phase, and structural parameters were determined for this phase. The morphology of the particles did not present significant differences on shape and size, demonstrating the reproducibility of the synthesis methods. Infrared to visible upconversion as well as infrared emissions at 1550nm were detected, suggesting that energy transfer processes from Yb3+ to Er3+ are predominant in Gd2O3:Yb3+:Er3+:Tm(3+)samples. The results pointed out the potential of Gd2O3:Yb3+:Er3+:Tm3+ as a material for solar concentrators and optical telecom C-band (1550nm) applications.
Keywords: PEG; up-conversion; Er3+:Tm3+:Yb3+; Gd2O3; infrared emission